Stable Na Plating and Stripping Electrochemistry Promoted by In Situ Construction of an Alloy‐Based Sodiophilic Interphase - Tang, Shuai; Zhang, Yi‐Yang; Zhang, Xia‐Guang; Li, Jun‐Tao; Wang, Xue‐Yin; Yan, Jia‐Wei; Wu, De‐Yin; Zheng, Ming‐Sen; Dong, Quan‐Feng; Mao, Bing‐Wei (Advanced materials (Weinheim), 2019)
Sodium metal anodes are poor due to the reversibility of Na plating/stripping, which hinders their practical applications. A strategy to form a sodiophilic Au–Na alloy interphase on a Cu current collector, involving a sputtered Au thin layer, is shown to enable efficient Na plating/stripping for a certain period of time. Herein, electrochemical behaviors of Na plating on different substrates are explored, and it is revealed that the sodiophilic interphase can be achieved universally by in situ formation of M–Na (M = Au, Sn, and Sb) alloys during Na plating prior to Na bulk deposition in the initial cycle. Moreover, it is found that repetitive alloying–dealloying leads to falling‐off of thin film sodiophilic materials and thus limits the lifespan of efficient Na cycling. Therefore, an approach is further developed by employing particles of sodiophilic materials combined with the control over the cutoff potential, which significantly improves the stability of Na plating/stripping process. Especially, the low‐cost Cu@Sn‐NPs and Cu@Sb‐MPs composite current collectors allow Na plating and stripping to cycle for 2000 and 1700 times with the average efficiency of 99.9% at 2 mA cm−2. Stable Na plating/stripping electrochemical behaviors are achieved by using the in situ formed sodiophilic sodium‐metal (metal = Au, Sn, Sb) alloy interphase. By simultaneous control over the stripping cut‐off potential and employment of anchored metal particles, Na plating/stripping cycling is extended to 2000 times at 2 mA cm−2 with an average Coulombic efficiency of 99.9% on the sodium‐metal alloy‐based interphase.